Characterization of Invasive Neisseria meningitidis from Atlantic Canada, 2009 To 2013: With Special Reference to the Nonpolysaccharide Vaccine Targets (Pora, Factor H Binding Protein, Neisseria Heparin-Binding Antigen and Neisseria Adhesin A) - Raymond SW Tsang; Dennis KS Law; Rita R Gad; Tim Mailman; Gregory German; Robert Needle (Canadian Journal of Infectious Diseases and Medical Microbiology)
BACKGROUND: Serogroup B Neisseria meningitidis (MenB) has always been a major cause of invasive meningococcal disease (IMD) in Canada. With the successful implementation of a meningitis C conjugate vaccine, the majority of IMD in Canada is now caused by MenB.